'There's more to a person than what's in front of you': Nursing students' experiences of consumer taught mental health education. (5th April 2019) - Happell, Brenda; Waks, Shifra; Bocking, Julia; Horgan, Aine; Manning, Fionnuala; Greaney, Sonya; Goodwin, John; Scholz, Brett; van der Vaart, Kornelis Jan; Allon, Jerry; Granerud, Arild; Hals, Elisabeth; et al.
Abstract: Holistic and person‐centred nursing care is commonly regarded as fundamental to nursing practice. These approaches are complementary to recovery which is rapidly becoming the preferred mode of practice within mental health. The willingness and ability of nurses to adopt recovery‐oriented practice is essential to services realizing recovery goals. Involving consumers (referred herein as Experts by Experience) in mental health nursing education has demonstrated positive impact on the skills and attitudes of nursing students. A qualitative exploratory research project was undertaken to examine the perspectives of undergraduate nursing students to Expert by Experience‐led teaching as part of a co‐produced learning module developed through an international study. Focus groups were held with students at each site. Data were analysed thematically. Understanding the person behind the diagnosis was a major theme, including subthemes: person‐centred care/seeing the whole person; getting to know the person, understanding, listening; and challenging the medical model, embracing recovery. Participants described recognizing consumers as far more than their psychiatric diagnoses, and the importance of person‐centred care and recovery‐oriented practice. Understanding the individuality of consumers, their needs and goals, is crucial in mental health and all areas of nursing practice. These findings suggest that recovery, taught by Experts by Experience, is effective and impactful on students' approach to practice. Further research addressing the impact of Experts by Experience is crucial to enhance our understanding of ways to facilitate the development of recovery‐oriented practice in mental health and holistic and person‐centred practice in all areas of health care.